The Effect of Dental Adhesive Composition and Etching Mode on Microleakage of Bonding Agents in Primary Molar Teeth - Baharan Ranjbar Omidi; Soolmaz Heidari; Fatemeh Farahbakhshpour; Elham Tavakolian Ardakani; Monirsadat Mirzadeh (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: The dilemma of microleakage at the composite-tooth interface is still a major challenge in operative dental practice. Purpose: This study aimed to compare the microleakage of universal adhesive with self-etch and total-etch bonding strategies for restoration of class-II primary molar cavities. Materials and Method: This in vitro, experimental study was conducted on 75 extracted primary molars. Class-II cavities were prepared in mesial or distal surfaces. The teeth were randomly divided into five groups of Adper Single Bond 2 (3M ESPE; St Paul, MN, USA), Clearfil SE Bond (Kuraray Noritake, Osaka, Japan), G-Bond (GC Corp., Tokyo, Japan), G-Premio Bond (GC Corp., Tokyo, Japan) with total-etch mode and G-Premio Bond with self-etch mode. Cavities were also restored with Nano-hybrid resin composite (Grandio, VOCO, Cuxhaven, Germany) and incubated for 24 hours, followed by thermocycling at 1500× between 5-55°C within a dwell time of 20 seconds. Later, the cavities were placed in 1M silver nitrate solution and evaluated under a stereomicroscope. Finally, microleakage was assessed quantitatively and qualitatively. One tooth in each group was prepared and evaluated under a scanning electron microscope (SEM). Data were analyzed using One-way ANOVA, Tukey's post hoc test and Chi-square test (p< 0.05). Results: The microleakage values were significantly different in the study groups (p< 0.05). The highest level of microleakage was noted in G-Bond and the lowest in G-Premio Bond with total etching. There was a significant correlation between the qualitative and quantitative measurements of microleakage. Conclusion: The G-Premio Bond yielded acceptable results in terms of microleakage in total-etch and self-etch modes. However, additional etching is recommended to improve the quality of bonding.